(untitled) (Universal International Scientific Journal, 2026)
This work aimed to identify and analyze steroids in the aboveground part of the plant Atrapahaxis spinosa L. Biologically active substances were isolated from the plant raw material by extraction method and studied using high-performance liquid chromatography. According to the results of chromatographic analysis, the presence of turkesterone and ecdysterone was determined. The results of the study confirm that this plant is promising as a pharmacologically valuable raw material.